The Role of Transformational Leadership in Enhancing Discipline Among Educators and Educational Staff in Islamic Educational Institutions - Afandi, Afandi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
This study aims to analyse the influence of transformational leadership on implementing discipline in Islamic schools. The study employs a qualitative approach using in-depth interviews, observations, and document analysis at MTS Saiful Ulum, a secondary Islamic school under the Ministry of Religious Affairs. The research participants consist of 20 individuals, including the principal, vice principals, educators, and administrative staff, who are directly involved in leadership and discipline enforcement. The findings indicate that the principal's transformational leadership fosters effective communication, enhances teacher accountability, and strengthens role modeling in discipline implementation within the school. The implications of this study encompass both practical and theoretical aspects. Practically, the findings provide insights for Islamic schools in developing leadership strategies based on transformational values to improve discipline. Theoretically, this study contributes to the literature on transformational leadership in Islamic education, particularly discipline management. The results of this study can serve as a foundation for policymakers in designing more effective leadership approaches to enhance discipline in Islamic schools.